Ionic dimers in He droplets: Interaction potentials for Li2+–He,Na2+–He, and K2+–He and stability of the smaller clusters - Bodo, Enrico; Yurtsever, E.; Yurtsever, M.; Gianturco, Francesco Antonio (AIP Publishing, 2006)
We present post Hartree-Fock calculations of the potential energy surfaces (PESs) for the ground electronic states of the three alkali dimer ions Li2+,Na2+, and K2+ interacting with neutral helium. The calculations were carried out for the frozen molecular equilibrium geometries and for an extensive range of the remaining two Jacobi coordinates, R and θ, for which a total of about 1000 points is generated for each surface. The corresponding raw data were then fitted numerically to produce analytic expressions for the three PESs, which were in turn employed to evaluate the bound states of the three trimers for their J=0 configurations: The final spatial features of such bound states are also discussed in detail. The possible behavior of additional systems with more helium atoms surrounding the ionic dopants is gleaned from further calculations on the structural stability of aggregates with up to six He atoms. The validity of a sum-of-potential approximation to yield realistic total energies of the smaller cluster is briefly discussed vis-a-vis the results from many-body calculations.
Keywords: Applied physics; Ab-initio; Physical chemistry; Interaction forces; Superfluid-helium droplets; Physical chemistry; Applied physics; Superfluid-helium droplets; Ab-initio; Interaction forces